Axé in movement in the religious market: Umbanda in decline, candomblé in ascension - Reginaldo Prandi (Anuac, 2015)
The article describes a peculiar dynamics of the Brazilian religious market: the rise and the decline of the cults of African origin. According to the data of several censuses, from 1940 to 2010, beside a slight, but constant, decline of Catholic followers, there was at first a vertiginous rise of umbanda, an “extremely Brazilian” syncretism, then a re-discovery of candomblé, considered as a specifically “afro” cult, and finally a dramatic loss of believers, due to various reasons. Primarily the aggressiveness of the Evangelical churches, which regards the “afro” deities as the representation of the devil; the extraordinary economic means of the same sects that are able to monopolize the media; the proverbial tolerance, the flexibility and the tendency of including instead of fighting different creeds which is typical of the polytheisms; these features are absolutely inadequate to face such a competitive religious market.